Who Gets the Catch? How Conventional Catch Attribution Frameworks Undermine Equity in Transboundary Fisheries - Davis, Ruth A.; Hanich, Quentin; Haas, Bianca; Cisneros-Montemayor, Andrés M.; Azmi, Kamal; Seto, Katherine L.; Swartz, Wilf; González-Espinosa, Pedro C.; Colléter, Mathieu; Adams, Timothy J. H. (Frontiers in Marine Science, 2022)
The focus on flag States for the purpose of attributing fisheries catch is inconsistent with the assignment of sovereign rights to coastal States under international law and undermines equity in contemporary quota allocation negotiations. We propose modernizing reporting frameworks to include zone-based reporting of fish catches to more equitably present data, ensure consistency with the Law of the Sea, and better support the realization by developing coastal States of their development aspirations consistent with SDG 14, Life Below Water. States are already required to collect the data necessary to support this change, and many regional fisheries management authorities already do so. Reforms to data collection and reporting mechanisms should support zone-based catch attribution as a central feature of negotiations around access to future fishing opportunities on shared resources. Doing so will ensure that the sovereign rights of developing coastal States are properly accounted for and implemented.